Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Perusahaan - Nur Fauziah; Teguh Setiawan (Jurnal Aplikasi Bisnis, 2017)
This study aimed to investigate the influence of good corporate implementation to company performance. Good Corporate Governance, while the company's performance is measured by the retun on equity, net profit margin, Tobins'Q. The analysis method used is a simple regression. This study uses empirical data from the Indonesia Stock Exchange with a sample of 36 companies for the period 2008-2011.Based on results of hypothesis testing using t-test statistics with a confidence level of 95% and a = 5% can he concluded that the first look at the effect of the application of the index GCG of the ROE and the results obtained applying the index value of 0.788, which means GCG insignificant and Ho received. The furthur testis tosee the effect of the application of NPM GCG index and index values obtained results GCG implementation of 0.021, which means significant and Ho is rejected. While last testing is to see the effect of the implementation of good corporate governance index and the obtained results Tobins'Q index value of 0.027 GCG implementation, which means significant and Ho is rejected.